Efficacy of biopesticides and fungicides against brown rot on cherry ( Prunus avium ) and plum ( Prunus domestica ) - Nattawut Rungjindamai; P. Jeffries; Xiangming Xu (Biocontrol Science and Technology, 2025)
Cherry and plum are prone to brown rot diseases. Synthetic fungicides are still the main management tool to control brown rot but there is a need to develop eco-friendly methods. Five commercial biopesticides including BioPK (Trichoderma viride, T. harzianum and T. longibranchum), BoniProtect (Aureobasidium pullulans), Trianum (T. harzianum), PreStop (Gliocladium catenulatum) and Serenade (Bacillus subtilis) along with Indar (fenbuconazole, a synthetic fungicide) were tested against Monilinia laxa which products applied before and after pathogen inoculation. Indar completely inhibited brown rot development. Serenade partially inhibited M. laxa when applied before pathogen inoculation. The efficacy of two indigenous strains (B. subtilis B91 and A. pullulans Y126) were evaluated under ambient conditions or 1°C; Indar and Serenade were used as control treatments. Cherry and plum were first treated with specific products, then wounded and inoculated with M. laxa. Indar completely inhibited M. laxa under both conditions. Under ambient conditions, only B91 reduced the incidence of disease. When stored at 1°C for 4 weeks, all biocontrol treatments reduced the incidence of disease. However, when fruits were left under ambient conditions for an additional 1 week, the incidence of disease did not differ between treatments. Post-harvest application of biopesticides under 1°C was studied with Rovral used as a control. Cherry and plum were submerged into individual treatments and stored at 1°C for 6 weeks. Rovral reduced the incidence of disease, whilst all biopesticides did not. In conclusion, Serenade, B91 and Y126 can partially inhibit M. laxa when applied before pathogen infection. The present study supports that these biocontrol proeducts should be used pre-harvest to reduce the extent of fruit latent infection by M. laxa, and an effective post-harvest cold chain management should be implemented to delay/minimise rot development.
Keywords: Plant Pathogens and Fungal Diseases; Forest Insect Ecology and Management; Banana Cultivation and Research